PENERAPAN ETIKA BISNIS DALAM MELAKUKAN TRANSAKSI PENJUALAN DI PASAR TRADISIONAL KOTA LANGSA MENURUT PERSPEKTIF ETIKA BISNIS ISLAM - firdaus Muhammad (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2019)
Ethics is a study of the legitimate and correct deeds and moral choices made by a person. In Greek is also known as ethos, which means custom habits. While in Arabic ethics is also known as Akhlak which means morality, temperance, conduct or character. Simply put, business ethics means learning about which is good/bad, right/wrong in the business world based on the principles of morality. This research is backed by the habit of sellers/traders in the market of Langsa city in the application of business ethics in Islam that emphasized on the ethics of trading. The purpose of this research is to know how an objective picture of the implementation of business ethics in conducting sales transactions in the traditional market of the Langsa city, and how Islamic reviews on the application of ethical trading in conducting Buy and sell transactions in the market. This research is a field research. The results of this research show that the implementation of trading transactions in the market of Langsa city has been executed well and is seen from two variables used two variables (attitudes of faith and habits) dominant show agreed with each A given statement. This indicates that business ethics in sales transactions that have been applied by traders are derived from the hereditary inheritance from parents (parental advice) or obtained by self-taught (natural) with ethical consideration and Unethical.